Misinterpretation of a skin fold artifact as pneumothorax on the chest x-ray of a trauma patient in Korea: a case report - Yoojin Park; Eun Young Kim; Byungchul Yu; Kunwoo Kim (Journal of Trauma and Injury)
Misinterpreting radiographic findings can lead to unnecessary interventions and potential patient harm. The urgency required when responding to the compromised health of trauma patients can increase the likelihood of misinterpreting chest x-rays in critical situations. We present the case report of a trauma patient whose skin fold artifacts were mistaken for pneumothorax on a follow-up chest x-ray, resulting in unnecessary chest tube insertion. We hope to help others differentiate between skin folds and pneumothorax on the chest x-rays of trauma patients by considering factors such as location, shape, sharpness, and vascular markings.